Apparent seronegative maternal shingles with post‐natal mother‐to‐baby transmission of varicella zoster virus. Issue 4 (11th December 2017) - Pan, Lin; Singh, Nitesh; Cannon, Ruth; Fawke, Joe; Tang, Julian W.
Abstract : We present an unusual case of varicella zoster (VZ) virus IgG negative, yet clinically apparent, maternal shingles, which prompted the administration of VZ immunoglobulin to the newborn. The mother had no previous VZ vaccination. Eleven days later the baby developed a primary VZ infection, with only mild disease, likely as a result of the VZ immunoglobulin. The variable sensitivity of VZV IgG‐specific assays is well‐recognized. Thus, the ability of this particular VZV IgG assay to detect both maternal and infant VZV IgG, post‐natally, suggests that the earlier VZV IgG negative results were due to lower circulating levels of maternal antibody.